Analisis novel Pudarnya Pesona Cleopatra karya Habiburrahman El-Shirazy ditinjau dari aspek Sosiologi Sastra - Ryan Hidayat; Prima Pantau Putri Santosa (Universitas Ahmad Dahlan, 2019)
The purpose of the study are to assess described the extent to which aspects concerning the achievement of sociology of a literary work in the novels of pudarnya a charm cleopatra the work of habiburrahman el-shirazy .Planned in the methodology for in this research was a method of descriptive of an analysis of the contents of the , by portraying the aspect of sociology literature in the novels of pudarnya a charm cleopatra the work of habiburrahman el-shirazy .The results and of discussion to be addressed the data obtained from the of novels a charm pudarnya clepoatra the work of habiburrahman el-shirazy consisting of 51 in the picture to the .Of novels analyzed according on the aspects falling under sociology literature , which includes the sociology a literary work , 1 ) the element of a social system: a political system as many as 0 points , a system of belief 18 points , the economic system 9 points , and the system of education as many as 6 points , 2 ) value system as many as 20 points and a system of an idea 6 points , and 3 ) culture equipment as many as 3 points